2019
DOI: 10.3390/genes10040303
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Salt-Responsive MicroRNAs in Vicia faba by High-Throughput Sequencing

Abstract: Salt stress has detrimental effects on plant growth and development. MicroRNAs (miRNAs) are a class of noncoding RNAs that are involved in post-transcriptional gene expression regulation. In this study, small RNA sequencing was employed to identify the salt stress-responsive miRNAs of the salt-sensitive Hassawi-3 and the salt-tolerant ILB4347 genotypes of faba bean, growing under salt stress. A total of 527 miRNAs in Hassawi-3 plants, and 693 miRNAs in ILB4347 plants, were found to be differentially expressed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…totally, 73 miRNAs (56 known miRNAs and 17 novel) were found to be regulated by salinity ( p < 0.01, Q < 0.05; Figure 5 ; Supplementary Data S3 ). Earlier studies have demonstrated that miR156, miR159, miR160, miR168, miR169, miR171, miR172, miR393, and miR396 were the major salt stress-regulated miRNAs in plants ( Alzahrani et al, 2019 ). All of these were also identified in our study, indicating the existence of common salt stress-related miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…totally, 73 miRNAs (56 known miRNAs and 17 novel) were found to be regulated by salinity ( p < 0.01, Q < 0.05; Figure 5 ; Supplementary Data S3 ). Earlier studies have demonstrated that miR156, miR159, miR160, miR168, miR169, miR171, miR172, miR393, and miR396 were the major salt stress-regulated miRNAs in plants ( Alzahrani et al, 2019 ). All of these were also identified in our study, indicating the existence of common salt stress-related miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that Hassawi-3 and ILB4347 differentially expressed 527 and 693 miRNAs, respectively. There was also a significant increase in 284 miRNAs in Hassawi-3 under control and a reduction in 243 miRNAs in ILB4347 plants during stress conditions [ 131 ].…”
Section: Plant Mirnas and Salt Stressmentioning
confidence: 99%
“…Alzahrani et al (2019) [ 116 ] uncovered 1220 salt-responsive miRNAs by small RNA sequencing of two contrasting faba bean ( Vicia faba ) genotypes for salinity stress response (ILB4347 tolerant and Hassawi-3 sensitive). The Hassawi-3 genotype had 284 upregulated and 243 downregulated miRNAs, while ILB4347 had 298 upregulated and 395 downregulated miRNAs in the control and under salinity stress.…”
Section: Role Of Ncrnas In Plant Adaptation To Salinity Stressmentioning
confidence: 99%
“…The Hassawi-3 genotype had 284 upregulated and 243 downregulated miRNAs, while ILB4347 had 298 upregulated and 395 downregulated miRNAs in the control and under salinity stress. The target gene(s) were predicted to encode TFs, laccases, superoxide dismutase, plantacyanin, and F-box proteins in addition to genes involved in hormone signal transduction, phosphatidylinositol signalling, and the MAPK signalling pathway [ 116 ].…”
Section: Role Of Ncrnas In Plant Adaptation To Salinity Stressmentioning
confidence: 99%